Innovation intermediation in a digital age: broadening extension service delivery in Ghana - Munthali, N. (Wageningen University & Research, 2020)
Classical extension focuses on linear transfer of technology. Globally, and in Ghana particularly, we have seen attempts to address the linearity of classical extension with the shift to broader extension service delivery approaches. From an innovation systems perspective innovation intermediation is suggested for extension organisations to function more effectively and respond to wider agricultural system constraints. This involves three broad facilitation roles which are demand articulation, matching demand and supply, and innovation process management. Both public and private extension service providers in Ghana are transitioning towards broader extension approaches, but these efforts are hampered by human and financial resource constraints. At the same time there is emphasis on exploring new Information and Communication Technologies’ (ICTs) potential to improve and upscale extension service delivery. However, there is limited knowledge on new ICTs’ potential and contribution to facilitating innovation intermediation. Taking in account that new ICTs can enable new ways of connecting people and sharing information, the thesis investigates the opportunities and role of new ICTs in supporting innovation intermediation in the Ghanaian extension system using a socio-technical perspective and a mixed methods research approach. The study finds that of the types of technologies functioning in the Ghanaian agricultural system there are opportunities for Interactive Voice Response (IVR) outbound, Data Management (DaM) and social media messaging technology to support innovation intermediation. Through interviews with extension organisation staff and observing field agents, the study finds DaM technologies can facilitate location-based farmer database development and support farmers’ (tacit) needs identification as well as intervention planning and advice tailoring. Beyond these organisations, an experts’ consensus building survey and interviews with farmers show that private sector led IVR interventions can provide farmers with immediate access to information (advice, weather, prices, pest threats). Further, by observing and interviewing actors on more informal social media messaging platforms it was established that these platforms can support the coordination of extension activities, timely pest and disease monitoring and knowledge sharing among extension staff and subject matter specialists to enable individual-centred learning and problem solving. Despite this potential, the study also shows that new ICTs’ inherent technical features do not determine their application, but social factors (human abilities and preferences, identity management, sociopolitical influences and the wider institutional environment) shape their use. Therefore, the potential of DaM and IVR outbound technologies are not realised, and the technologies identified have the potential to or contribute to innovation intermediation activities as they complement human intermediaries (public extension agents) and conventional communication mechanisms (face-to-face settings and radio). The implications of these findings for extension practice and policy are that contextual considerations are made, and participatory technological design engaged to foster technological access and realise new ICTs’ potentials. Another recommendation is that combinations of new and classical media, face-to-face settings and human intermediaries are explored such that new ICTs are integrated into the existing communication landscape of extension systems based on where they add value - as this is where huge opportunities for facilitating innovation intermediation lie.